E-Service Quality pada Pelayanan Kependudukan Elektronik Alpukat Betawi Pemerintah Provinsi DKI Jakarta - Siti Nurjanah; Wahyu Mahendra (Universitas Merdeka Malang, 2022)
Alpukat Betawi is an electronic public service provided to facilitate population administration services in the DKI Jakarta Province. However, not all electronic services have good service quality. This can be seen from some problems such as systems that are not running well and cannot be accessed on time, as well as data security that is not free from dangerous risks. This study aims to analyze the Betawi avocado using an e-service quality approach. The research approach carried out in this study is quantitative with a mixed-method data collection technique, which combines quantitative and qualitative methods through surveys, in-depth interviews, and literature studies. The results of this study indicate that the e-service quality on Alpukat Betawi electronic population service in the DKI Jakarta Provincial Government is in the good category (92%). This is evident from the four dimensions of e-service quality proposed by Papadomichelaki Mentzas (2012) which belong to the good category.